Effect of ethyl alcohol wet bonding on shear bond strength in orthodontic brackets - An In vitro study - Nishanth Sivakumar; Dilip Srinivasan; Sushil Chakravarthi; Ravi Kannan (Wolters Kluwer Medknow Publications, 2023)
Aim: To evaluate the effect of ethyl alcohol wet bonding on the shear bond strength of orthodontic brackets. Materials and Methods: 90 premolar teeth were collected and divided into 6 groups - conventional dry, conventional wet, MIP dry, MIP wet, ethanol dry, and ethanol wet. The teeth were bonded as per the requirements for each group. The teeth were then immersed in water to ensure complete polymerization. Shear bond strength was evaluated using a UTM machine and the ARI scores were also noted. Statistical analysis was done for the SBS and ARI scores obtained. Results: The highest SBS was obtained with conventional dry and the least SBS was obtained with conventional wet groups. The SBS of ethanol wet bonding was significantly less than that of the MIP wet group but was significantly more than the conventional wet group. ARI scores also suggested that there is more cohesive failure than adhesive failure in the wet MIP and ethanol groups. Conclusion: The mean SBS (6.5 MPa) was within the optimal bond strength as per the study by Reynolds et al. (1976). Ethanol can be used as a cheaper alternative to MIP.